Circuit Breakers in Low- and Medium-Voltage DC Microgrids for Protection against Short-Circuit Electrical Faults: Evolution and Future Challenges - Bayron Perea-Mena; Jaime A. Valencia-Velasquez; Jesús M. López-Lezama; Juan B. Cano-Quintero; Nicolás Muñoz-Galeano (Applied Sciences, 2021)
This paper deals with circuit breakers (CBs) used in direct current microgrids (DCMGs) for protection against electrical faults, focusing on their evolution and future challenges in low voltage (<1.5 kV) and medium voltage (between 1.5 kV and 20 kV). In recent years, proposals for new circuit-breaker features have grown. Therefore, a review on the evolution of circuit breakers for DCMGs is of utmost importance. In general terms, this paper presents a review concerning the evolution of circuit breakers used in DCMGs, focusing on fuses, mechanical circuit breakers (MCBs), solid-state circuit breakers (SSCBs), and hybrid circuit breakers (HCBs). Their evolution is presented highlighting the advantages and disadvantages of each device. It was found that although modern circuit breakers have begun to be commercially available, many of them are still under development; consequently, some traditional fuses and MCBs are still common in DCMGs, but under certain restrictions or limitations. Future challenges that would allow a successful and adequate implementation of circuit breakers in DCMGs are also presented.